Characterization of multitype colonies originating from porcine blastocysts produced in vitro - Oh, Jong-Nam; Jeong, Jinsol; Lee, Mingyun; Choe, Gyung Cheol; Lee, Dong-Kyung; Choi, Kwang-Hwan; Kim, Seung-Hun; Lee, Chang-Kyu (Frontiers in Cell and Developmental Biology, 2022)
Many embryonic stem cells have been induced from pre-implantation blastocyst to study the specification of early lineages. Various cell lines were established using chemicals including excessive inhibitory molecules. Also, previous studies aimed to purify cell populations representing single embryonic lineage from a protocol. In this study, we used a novel culture condition to induce cells from blastocyst seeding and analyzed characteristics. Next, signaling inhibitors were introduced during the cell culture period. Further, we investigated RNA sequencing of cell types. Each type of cell population showed distinct morphology and reactivity on alkaline phosphatase. Marker proteins enabled to distinguish each cell type in immunocytochemistry, and genes like Sox17, Gata4, Gata6, T, and Cdx2 showed applicability for discrimination of cell types. Signaling inhibitors suppressed the production of some cell types, and gene expression and marker protein patterns were collapsed. RNA-seq revealed cell-type-specific genes and the correlation of samples. In conclusion, four types of cells could be induced from the porcine embryo, and they could be isolated with a single protocol. Our data will help and promote the study about lineage segregation based on embryonic cells.